2012
DOI: 10.1097/prs.0b013e3182402e8e
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Primary Cleft Rhinoplasty on Secondary Cleft Rhinoplasty in Patients with Unilateral Cleft Lip–Cleft Palate

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 13 publications
1
44
0
Order By: Relevance
“…27 Proponents of primary cleft rhinoplasty suggest that primary treatment reduces the severity of the nasal deformity, reduces the number of revision surgeries required in adulthood, and may lessen psychosocial impact of deformity during development. [28][29][30] Historically, cleft surgeons were influenced by animal studies that suggested that rhinoplasty (before full skeletal maturity) could induce long-term nasal growth inhibition due to disruption of nasal growth centers. 31 There is a lack of rigorous evidence pertaining to this clinical question.…”
Section: Surgical Timing and Techniquesmentioning
confidence: 99%
“…27 Proponents of primary cleft rhinoplasty suggest that primary treatment reduces the severity of the nasal deformity, reduces the number of revision surgeries required in adulthood, and may lessen psychosocial impact of deformity during development. [28][29][30] Historically, cleft surgeons were influenced by animal studies that suggested that rhinoplasty (before full skeletal maturity) could induce long-term nasal growth inhibition due to disruption of nasal growth centers. 31 There is a lack of rigorous evidence pertaining to this clinical question.…”
Section: Surgical Timing and Techniquesmentioning
confidence: 99%
“…86,87 The Tajima technique utilizes a reverse-U incision along the alar margin and redistributes the overhanging skin of the alar margin to augment deficient lining. 90 The potential risks of a primary rhinoplasty include iatrogenic deformity to the skin envelope and the introduction of scarring which may complicate subsequent interventions. 89 The goals of primary rhinoplasty include improving nasal contour, symmetry and nasal tip projection, with relocation of the caudal nasal septum.…”
Section: Primary Nasal Correctionmentioning
confidence: 99%
“…10 A long term study made by Haddock et al concluded that primary nasal reconstruction performed with cleft lip repair makes the nasal tip more symmetric without affection of nose growth. 11 In relation to the growth of the nose, Anderl et al 12 concluded in their study a lack of growth retardation using primary rhinoplasty. This study confirms these observations and concluded that primary tip rhinoplasty did not significantly improve symmetry at 5 years and did not affect the growth of the nose.…”
mentioning
confidence: 97%